Sima'an Tahfizh Al-Qur'an at Manbaul Ulum Islamic Boarding School, Banjar District - Rojiyah, Mawaddatur; Basir, Abd.; Yahya, M. Daud; Muhrin, Muhrin; Syahbudin , Akhmad (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
The study aims to evaluate whether the practice of simian, which involves reciting memorized verses of the Qur'an before an audience of peers and instructors, is an effective means of maintaining Catalan or memorization and improving recitation fluency. The method used in this study is a case study, with data collected through observation, interviews, and documentation. Female students participating in similar activities at the Islamic Boarding School were selected as subjects. The study findings indicate that simian is an effective method of maintaining the robustness of memorizing the Qur'an and minimizing mistakes in recitation. The participants in the simian activities significantly improved their recitation fluency and memorization strength. This improvement was attributed to the muraja'ah or regular repetition of memorized verses in preparation for a similar activity. The repetition of memorized verses enabled the participants to maintain fluency and accuracy in recitation, which they demonstrated during similar activities. The study also identified factors that supported and inhibited the effectiveness of similar activities.